2020
DOI: 10.21608/besps.2019.14512.1026
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin mitigates liver injury in a rat model of liver cholestasis

Abstract: Background: cholestasis is a prevalent health problem associated with liver oxidative stress, inflammation, and fibrosis. Quercetin has been shown to afford a beneficial effect in a variety of liver diseases. This study was designed to investigate the potential protective effect of quercetin on liver cholestasis and the possible underlying mechanisms in a rat model of bile duct ligation (BDL). Methods: This study was carried out on adult male rats which were randomly divided into: Sham-operated, BDL and BDL-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…TNF- α and TGF- β as proinflammatory cytokines signal the expression of several inflammatory mediators and the regulation of the inflammatory response, which are increased by oxidative stress [ 40 , 41 ]. Recent findings showed that hepatic TNF- α and TGF- β genes expression was increased in liver injury [ 36 , 42 ], which is consistent with our results. In our work, OM extract reduced hepatic TGF- β gene expression, which was increased by BDL-V.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…TNF- α and TGF- β as proinflammatory cytokines signal the expression of several inflammatory mediators and the regulation of the inflammatory response, which are increased by oxidative stress [ 40 , 41 ]. Recent findings showed that hepatic TNF- α and TGF- β genes expression was increased in liver injury [ 36 , 42 ], which is consistent with our results. In our work, OM extract reduced hepatic TGF- β gene expression, which was increased by BDL-V.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that the administration of medicinal plants and natural compounds with antioxidant activity such as hydroalcoholic extract of Watercress [ 20 ], Ziziphus mauritiana leaf [ 35 ], polydatin [ 31 ], quercetin [ 36 ], and Marjoram oil [ 37 ] can protect the liver against oxidative damage caused by cholestasis. SOD and CAT are antioxidants that prevent the production of free radicals and also work as part of the first line of defense in the living cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CAT, which plays a vital role in decomposing H 2 O 2 into O 2 and H 2 O, GPx is a critical enzyme that catalyzes the reduction of H 2 O 2 (46,47). Increased GPx and SOD levels in liver tissue can decrease oxidative stress-mediated injury in cholestatic animal models (48,49). Our findings showed that OD therapy in BDL-induced cholestatic rats significantly promotes the functions of SOD and GPx in liver tissue.…”
Section: Discussionmentioning
confidence: 55%
“…Serum levels of liver enzymes ALT, AST, and ALP are measured to track liver damage so that their increased levels can be attributed to liver cell dysfunction ( 35 ). Several studies showed a remarkable elevation in the serum levels of the above mentioned biomarkers associated with significant histopathological changes after BDL surgery ( 6 36 ). For instance, one study showed that histopathological changes were associated with an elevation in serum level of ALP during BDL surgery ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bile duct ligation (BDL) is a reliable experimental model for induction of cholestasis ( 5 ). The plasma levels of major liver enzymes such as alkaline phosphatase (ALP), aspartate aminotransferase (AST), and alanine aminotransferase (ALT) elevated following BDL-induced hepatocyte injury in rats ( 6 ).…”
Section: Introductionmentioning
confidence: 99%